Determination of Microplastics in Sediments of the Mashcón River, Cajamarca - Perú 2023 - Peña Velasquez, Pedro Isac; Licapa-Redolfo, Gladys S. (LACCEI, 2024)
The fundamental purpose of this research is to evaluate the amount of microplastics found in the sediments of the Mashcón River, the methodology used for the determination and identification of microplastics was by difference in densities with a solution of calcium chloride (CaCl2), physical analyzes were carried out at 13 sampling stations (E1, E2, E3, E4, E5, E6, E7, E8, E9, E10, E11, E12 and E13), in the stations where the greatest amount of microplastics were found were E6 (23MPs ), E7 (23MPs), E8 (29MPs) and E12 (23MPs), finding a total of 216 microplastics in the 13 m2 * 20 cm depth of the study area, according to the standardized and applied procedures, the predominant color found was the blue and transparent, according to their size classification 1mm-5mm. Based on the findings and analyzes carried out, it can be concluded that the Mashcón River is contaminated by microplastics. This presence represents a silent threat to the life of this important river, highlighting the urgent need to address and mitigate the effects of microplastic pollution in this aquatic ecosystem.